Tax Avoidance, Endogenous Social Norms, and the Comparison Income Effect - Alessandro Balestrino (University of Copenhagen, Economic Policy Research Unit (EPRU), 2005)
We present a model of income tax avoidance with heterogenous agents, assuming the presence of a comparison income effect and of a psychic cost (disutility) of tax dodging. We analyse the policy preferences of the agents, and identify a median-voter political equilibrium. Paralleling previous results in the optimal taxation literature, we show that the comparison income effect calls for a high degree of progressivity of the income tax; additionally, we find that this tendence is strenghtened by the psychic cost of avoidance. We then investigate the source of the stigma attached to the act of avoidance and find that such stigma is motivated by the desire to make redistribution more effective, and that it is enhanced by the income comparison effect.
Keywords: 330; Steuervermeidung; Steuersystem; Einkommensverteilung; Wirtschaftsmodell; Soziale Norm